Demonstration of a 650 °C operating high-performance metal-supported solid oxide fuel cell using a Gd-doped CeO2 electrolyte, Ni anode and Sm(Ba0.5Sr0.5)Co2−xFexO5+δ–Ce0.9Gd0.1O2−δ cathode - Lu, Fei-Fei; Jia-Hong, Li; Ma, Qi; Chang-Jiu, Li; Venkataraman Thangadurai; Cheng-Xin, Li (Journal of materials chemistry. A, Materials for energy and sustainability, 2025)
Metal-supported solid oxide fuel cells (MS-SOFCs) exhibit numerous advantages, including thermal cycle stability, rapid start-up and lower costs. However, the slow oxygen reduction reaction (ORR) at the cathode, especially at intermediate-low temperatures, poses a critical challenge to the development of MS-SOFCs. Herein, we report a synergistic effect of co-doping in a cation-ordered double perovskite-type material, Sm(Ba0.5Sr0.5)Co2−xFexO5+δ (SBSCFx), which has enhanced catalytic activity for ORR and chemical compatibility with Ce0.9Gd0.1O2−δ (GDC). X-ray photoelectron spectroscopy and thermogravimetric analysis were used to examine how Fe-doping in SBSCFx impacts the functional properties. A composite cathode with GDC was further prepared to enhance thermal compatibility with GDC, which effectively reduces the thermal expansion of the SBSCFx cathode from 23.35 × 10−6 K−1 to 15.04 × 10−6 K−1. The electrochemical results of symmetrical cells and the DRT fitting analysis demonstrate that the SBSCFx-GDC composite cathode exhibits strong ORR activity. Notably, the SBSCF10-GDC composite cathode achieves a remarkably low polarization resistance of 0.05 Ω cm2 at 650 °C. The metal-supported single cell with the SBSCF10-GDC cathode exhibited an open-circuit voltage of 0.85 V and showed a peak power density of 833 mW cm−2 at 650 °C. Furthermore, its stability during long-term cell operation highlights its potential as a cathode for intermediate-low temperature metal-supported SOFCs.